Assessment and Evaluation in Higher Education - Fernandes, Sandra Raquel Gonçalves; Abelha, Marta; Ferreira-Oliveira, Ana Teresa (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on research and practice concerning assessment and evaluation in higher education, crucial processes for the advancement of higher education. The different dimensions and forms of assessment within higher education, the impact of assessment methods on students' learning processes and approaches to learning are of particular interest. Special attention is given to assessment methods and purposes, assessment rubrics and the assessment of learning outcomes (knowledge and skills). Research on the challenges, strengths, and opportunities of online and virtual assessment, active learning approaches and new pedagogical methodologies, based on student-centred assessment practices, is also explored and discussed in this reprint.